2022
DOI: 10.1039/d2gc00853j
|View full text |Cite
|
Sign up to set email alerts
|

Integration of upcycling and closed-loop recycling through alternative cyclization–depolymerization

Abstract: Currently, to address the problem of end-of-life plastics, scientific researchers are urgently looking for the future generation of polymers and technologies that contribute to upcycling and closed-loop recycling. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
0
17
0
4
Order By: Relevance
“…The resulting PMDO can be completely depolymerized by simple pyrolysis to recover the MDO. In 2022, wang et al [90] . used Brønsted acidic ionic liquid as a solvent/catalyst bifunctional agent to achieve linear PPDO ( l ‐PPDO) depolymerization and cyclization at a low temperature.…”
Section: Chemically Recyclable Polyestersmentioning
confidence: 99%
“…The resulting PMDO can be completely depolymerized by simple pyrolysis to recover the MDO. In 2022, wang et al [90] . used Brønsted acidic ionic liquid as a solvent/catalyst bifunctional agent to achieve linear PPDO ( l ‐PPDO) depolymerization and cyclization at a low temperature.…”
Section: Chemically Recyclable Polyestersmentioning
confidence: 99%
“…1–3 Extensive research focused on chemical recycling of polymers to monomers (CRM) has been devoted to enabling a circular plastics economy and sustainable development. 4–35 In a pioneering work, poly (γ-butyrolactone) from the ring-opening polymerization (ROP) of “non-polymerizable” butyrolactone was discovered to quantitatively depolymerize into its monomer γ-butyrolactone upon being heated at 220–300 °C for one hour, 4,36 manifesting the potential of its chemical recycling in the circular plastics economy and promoting the development of this field. However, most of the currently studied polymer systems have involved aliphatic polyesters 37–48 and chemically recyclable aromatic polyesters have been less extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, O -heterocyclic lactones are promising candidates to prepare closed-loop recyclable polyesters. The ROPs of 1,4-dioxan-2-one, 2,3-dihydro-5 H -1,4-benzodioxepin-5-one, and their derivatives have been reported to produce closed-loop recyclable polyesters. , For example, Zhu’s group reported that a class of aromatic cyclic ester monomers can be prepared from thiosalicylic acid and epoxides by a facile one-pot synthetic strategy . ROP of these monomers can afford aromatic–aliphatic polyesters with high molecular weights and narrow dispersities.…”
Section: Introductionmentioning
confidence: 99%